The adventures of Tom Sawyer - Twain, Mark 1835-1910 (Office of English Language Programs, 2005)
The adventures of Tom Sawyer stands aot as one of the great American novels, with adventure, humor, danger, and warmth. It is filled with characters that have become part of american culture: Tom, Huck Finn, Becky, Aunt Polly, and others